Micro encapsulation of Naproxen By Complex Coacervation and Aqueous Colloid Dispersion Part ( 1 ) - Ahmad N.Abood; Yehia I.Khalil (College of Pharmacy University of Baghdad, 2017)
Naproxen is a non steroidal anti inflammatory and antipyretic drug which has local irritation effect  on  the  stomach, and  unpleasant taste,  besides bad   flowability and light sensitivity .The drug was prepared as microcapsules by complex coacervation method using acacia-gelatin coating materials , and aqueous colloid polymer dispersion method ( ACPD ), using ethyl cellulose and sodium alginate coating materials . The results indicated that microcapsules prepared by 2:1  core:wall ratio is the best for both methods, with an average encapsulation efficiency (75%) and avarege yield (90%) . Moreover the drug release was affected mainly by core : ratio ,pH enviroment and method of microencapsulation . Key words: Naproxen,Microcapsule , Aqueaus colloid polymer dispersion